Postpartum fluoxetine increased maternal inflammatory signalling and decreased tryptophan metabolism: Clues for efficacy. (15th September 2020) - Qiu, Wansu; Duarte-Guterman, Paula; Eid, Rand S.; Go, Kimberly A.; Lamers, Yvonne; Galea, Liisa A.M.
Abstract: Perinatal depression (PND) affects approximately 15% of women, and de novo postpartum depression affects approximately 40% of PND cases. Selective serotonin reuptake inhibitors (SSRIs) are a common class of antidepressants prescribed to treat PND. However, the safety and efficacy of SSRIs have been questioned in both clinical and preclinical research. Here, using a preclinical rodent model of de novo postpartum depression, we aim to better understand neuroinflammatory cytokines and tryptophan mechanisms that may be related to SSRI efficacy. Rat dams were treated with high corticosterone (CORT; 40 mg/kg, s.c.) for 22 days in the postpartum period to simulate a depressive-like endophenotype. Concurrently, a subset of dams was treated with the SSRI, fluoxetine (FLX; 10 mg/kg, s.c.), in the postpartum period. We showed, consistent with previous studies, that although maternal FLX treatment prevented CORT-induced disturbances in maternal care behavior during the early postpartum, it failed to prevent the expression of CORT-induced passive coping behavior in the late postpartum. Furthermore, FLX treatment, regardless of CORT treatment, increased maternal hippocampal IL-1β, plasma CXCL1, and decreased maternal plasma tryptophan, 4′-pyridoxic acid, and pyridoxal concentrations. Maternal CORT treatment reduced maternal hippocampal IFN-γ, and both hippocampal and plasma TNF-α. Our work suggests that the limited efficacy of FLX in the late postpartum may be associated with elevated levels of the proinflammatory cytokine IL-1β in the maternal hippocampus, elevated plasma CXCL1, decreased plasma tryptophan concentration, and changes in vitamin B6 dependent tryptophan-kynurenine pathway. These findings suggest novel pathways for improving SSRI efficacy in alleviating perinatal depression. Highlights: Postpartum fluoxetine (FLX) increased hippocampal IL-1β and plasma CXCL1. Postpartum corticosterone (CORT) decreased TNF-α and IFN-γ in the hippocampus. Postpartum FLX did not prevent CORT-induced passive coping behavior. Postpartum FLX prevented CORT-induced changes in maternal behavior. Postpartum FLX decreased plasma tryptophan, 4′-pyridoxic acid, and pyridoxal levels.